THE ASSESSMENT OF THE ARTERIAL WALL HISTOMETRIC PARAMETERS CORRELATION WITH THE CLASSICAL RISK FACTORS FOR CARDIOVASCULAR DISEASES (СVD) / ARTERIAL HISTOMETRIC PARAMETERS CORRELATION WITH RISK FACTORS FOR СVD - Sergeevich Averkin, Nikita; Vladimirovna Latynova, Irina; Gennad'evna Fedorova, Mariya; Sergeevna Vishnyakova, Zhanna; Pavlovna Evseeva, Oksana; Valentinovna Komarova, Ekaterina; Vladimirovich Shilenkov, Aleksandr (Revista Inclusiones, 2020)
The research aim: to study the features of morphometric parameters of the arterial wall and their correlation with risk factors for the cardiovascular diseases. Methods: there were examined the carotid arteries of 106 deceased people aged 19 to 95 years without cardiovascular diseases detected during life or autopsy. There were two age groups: conditionally younger (men up to 45 years and women up to 55 years) and elder. The following morphometric parameters were measured: external (Dex) and internal diameters (Din), cross-sectional area of the arterial wall (Ssec), area of the arterial wall by external (SDex) and internal (SDin) diameters, thickness of the intima-media complex (IMT). The presence and area of the atherosclerotic lesion were assessed, and the Vogenvort (W) and Kernoghan (K) indexes were calculated.